السياسة العامة للبعثات في ليبيا: دراسة تقييمية 1969-2017 - أمنينة، عبير إبراهيم (جامعة بنغازي, 2018)
هدفت الورقة إلى تقييم السياسة العامة للبعثات المتبعة من قبل "أمانة التعليم العالي"(1969-2011) إبان النظام السابق، ووزارة التعليم العالي بعد انتفاضة فبراير (2011-2017)، وذلك من خلال تحليل مضمونها وتقييم أدائها وفقا لما تم إعلانه من أهداف. توصلت الدراسة والتي تم فيها تبني مدخل السياسات العامة بشكل رئيسي إلى أن الإجراءات التي تم أتباعها طيلة مرحلة الدراسة لا ينطبق عليها مفهوم السياسة العامة من حيث وضوح الأهداف وفعالية التنفيذ وتحقيق النتائج المرجوة والمتابعة والتقييم المستمرين. فما تم إقراره ووضعه موضع التطبيق خلال الفترة الزمنية الممتدة من (1969-2010)، أو‏ المرحلة التي تلتها (2011-2017)، يظل مجرد قرارات إيفاد مبعثرة لم يتم تنفيذها بناء على استراتيجية واضحة تتضمن تحديدا مسبقا ومدروسا للاحتياجات من كافة التخصصات لتحقيق أهداف محددة للسياسة العامة للبعثات، إنما جاءت مرتجلة، عشوائية، ومفتقدة للتخطيط والتقويم. The paper aimed to assess the policy of sending students abroad for study, followed by the Higher Education Secretariat (1969-2011) during the previous regime and the Ministry of Higher Education after February 2011-2017 by analyzing its content and evaluating its performance according to the declared objectives. The study concluded that the procedures followed throughout the study period do not apply to the concept of public policy in terms of clarity of objectives and effectiveness of implementation, and achieve the desired results and ongoing follow-up and evaluation. What has been adopted and put into effect during the period of time (1969-2010), or the subsequent phase (2011-2017), remains only scattered dispatch decisions that have not been implemented based on a clear strategy that includes pre-defined and studied needs for all disciplines, to achieve specific objectives of the assess the policy of sending students abroad for study, but came impromptu, random, and missing planning.
Keywords: السياسات الخارجية -- البعثات التعليمية -- التخطيط الإستراتيجي -- التعليم العالي -- الإدارة التربوية -- ليبيا